Synthesis of N-methoxy-N-methylaminocarbonyl-l, 4-benzoquinone: the First Quinone Carrying an N-methoxy-N-methylamino Group - Ahmad, Faujan (1988)
We report herein a four-step preparation of the title compound. Gentisic acid (1) was firstly converted into its diacetate (2) by treatment with acetic anhydride in the presence of concentrated sulfuric acid. Treatment of the diacetate with oxalyl chloride in dichloromethane in the presence of dimethylformamide followed by N-D-dimethyl-hydroxyamine hydrochloride and pyridine gave 2, 5-diacetoxy-Nmethoxy- N-methylbenzamide (3). Reaction of this with sodium hydrogen carbonate to generate the hydroquinone (4) followed by oxidation with silver oxide gave the desired quinone (5).